以文化为底蕴打造城市品牌的战略研究 = A study on the strategy of building city brand based on city culture - 吴显国 Wu, Xian Guo (2008)
This dissertation analyzes the current state and characteristics of city culture and brand. It clarifies the links between culture and city, and for the first time, defines the concept of city culture from the point of view of city management. Based on historical materialism, this dissertation discusses culture’s implelling effect and significance on social improvement and economy system.